Fantasy After Representation: D&D, Game of Thrones, and Postmodern World-Building. Issue 2 (July 2017) - Vu, Ryan
Abstract : My essay is premised on the observation that while canonical theories of fantastic genre fiction (fantasy, science fiction, horror) proposed by critics such as Tzetvan Todorov and Darko Suvin center on epistemic aporia, most recent examples in popular culture reject fundamental difference, alterity, and the unknown in favor of postmodern play within a limited set of generic conventions. I argue that today, tabletop roleplaying game systems (RPGs) provide a superior hermeneutic for understanding how the fantasy genre operates in mass culture than does traditional genre theory. After providing a brief overview of the historical development of fantasy gaming out of wargaming and mass market fantasy literature in the 1970s, I show how RPGs formalized fantasy's generic tropes into a modular system that enabled participants to produce fictions across and between genres. Through a reading of Poul Anderson's use of the "multiverse" trope in his novel Three Hearts and Three Lions, the notion that reality consists of an infinite number of interconnected worlds, I argue RPGs completed a reorientation toward the fantastic begun by mass-market fantasy literature. Epistemological concerns, distinctions between fantastic genres, and individual authorship are de-emphasized in favor of established formal conventions, a shift which encourages a participatory model of consumption and ease of transmission across diverse media. I then use the HBO adaptation of George R. R. Martin's Game of Thrones novels as an example of how this paradigmatic shift in the fantastic has moved beyond the niche markets of fantasy fiction and roleplaying games to manifest itself today as a hegemonic cultural norm.